Antiviral Effect of Ginsenoside Rb2 and Rb3 Against Bovine Viral Diarrhea Virus and Classical Swine Fever Virus in vitro - Tan, Bin; Giangaspero, Massimo; Sun, Na; Jin, Yinping; Liu, Kexin; Wang, Qianying; Cheng, Shipeng; Wang, Yingping; Zhang, Shuqin (Frontiers in Veterinary Science, 2021)
Bovine viral diarrhea virus (BVDV) and classical swine fever virus (CSFV) are members of the genus Pestivirus that cause disease in wild and domestic animal and responsible for extensive economic losses of livestock and biological industry. BVDV is also a significant laboratory contaminant. Currently, no effective antiviral therapeutics are available to control their infection. Ginsenosides, as major pharmacological ingredients in the plants of ginseng, have various biological activities. In the present work, the antiviral activity of 9 ginsenosides and other 3 saponins from Araliaceae plants was investigated against Pestivirus. Ginsenoside Rb2 and Rb3 showed low cytotoxicity and obvious antiviral effect. They were able to inhibit the replication and proliferation of BVDV and CSFV. In addition, our results suggest that the possible antiviral mechanism of Rb2 might be related to its ability to affect the translation of these viruses. Obtained results suggest that ginsenoside Rb2 and Rb3 have a potential for effective treatment against Pestivirus infection.